A review on observation of urban heat island in thermal remote sensing - Ibrahim, Illyani; Abu Samah, Azizan; Fauzi, Rosmadi (2017)
The climate experts have proposed various approaches and strategies to understand the causes of Urban Heat Island (UHI) phenomenon. The aim of this paper is to review the details concerning the themes of urban climate study and its measurement over a variety of cities. The paper discusses several approaches of thermal remote sensing study of different spatial resolution as well as satellite images. The researchers conclude with the development of an observation framework of the thermal remote sensing.